Emerging development in polymeric electrospun nanoscale mats for tissue regeneration: narrative review of the literature - Hamza Abu Owida; Muhammad Al-Ayyad; Jamal Al-Nabulsi; Nidal Turab; Mustafa Abdullah (Institute of Advanced Engineering and Science, 2023)
Tissue engineering is a cutting-edge discipline that brings together scientific and health-related, biological, and engineering principles in order to build tissue-engineered constructions able to restore or sustain the physiological properties of native tissue, or to marginally enhance those properties. This field is called